Plasma microRNA vary in association with the progression of Alzheimer's disease: Developing topics. (7th December 2020) - Guévremont, Diane; Tsui, Helen; Knight, Robert; Fowler, Christopher J; Masters, Colin L; Martins, Ralph N; Abraham, Wickliffe C; Tate, Warren P; Cutfield, Nick; Williams, Joanna M; ,
Abstract: Background: Early intervention in Alzheimer's disease (AD) requires development of an easily administered test able to identify those at risk. Focusing on microRNA robustly detected in plasma and standardizing the analysis, we sought to identify disease‐stage specific biomarkers. Method: Using TaqMan microfluidics arrays and a statistical consensus approach, we assessed plasma levels of 182 neurodegeneration‐related microRNA, in cohorts of amyloid‐positive, mild cognitive impairment and AD participants, relative to their respective controls. Result: Plasma microRNA were shown to be dynamically altered with AD progression. Distinct disease stage microRNA biomarkers were identified, and these were shown to predict membership of the groups (AUC >0.8). Bioinformatics demonstrated that these microRNA target known AD‐related pathways. Furthermore, a significant correlation was found between three microRNA and amyloid‐ß load. Conclusion: Our results show that microRNA signatures alter during the progression of AD, relate to the underlying disease pathology and may prove to be useful diagnostic markers.